TREATMENT OF PILLOUS ATRESIA IN CHILDREN. - Kodirova Ziyodakhon Avazbek qizi; Akramova Nozima Akramovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Esophageal atresia is the main congenital defect that requires urgent and strict medical care. This article is devoted to the analysis of modern methods of treating esophageal atresia in children. The paper discusses current approaches to the diagnosis and individual disease data, including surgery, emergency care, postoperative support, and rehabilitation. Particular attention is paid to the advantages and implementation of various methods for analyzing data from scientific publications and protocols obtained from Google Scholar, Scopus and other sources. The results of the study show an improvement in treatment outcomes due to modern surgical techniques and a comprehensive approach to postoperative support. However, further research is still needed.